TO THE ISSUE OF IDENTIFYING ILLEGAL ASSETS - Karapetian, Olga; Karapetian, Artem (SWorld-Ger Conference proceedings, 2025)
The article is devoted to the study of the implementation in Ukraine the best practices and standards of the European Union in the field of detection, search and management of assets obtained from corruption and other crimes. A comparative analysis in the